The survey of expression levels of virulent genes in Salmonella strains isolated in retail meats in Hanoi - Hoai Thu, Nguyen Thi; Viet, Nguyen Thanh; Minh, Nghiem Ngoc; Bich Thuy, Vo Thi (Academia Journal of Biology, 2018)
Salmonella is one of the major causes of food poisoning worldwide, especially in developing countries. The virulence of Salmonella is a complex process involving between their virulence factors and the host defenses. The purpose of this study was to detect virulent genes and to assess the level of expression of these genes in five Salmonella strains (including Enteritidis, Albany, Typhimurium, Hadar, and Derby), which were isolated from meat samples at the retail markets in Hanoi. As a result, Salmonella Enteritidis and Salmonella Typhimurium were 100% positive with seven virulent genes, e.g., spiA, spvB, sitC, sifA, sipB, pagC, and invA genes. Salmonella Hadar and Salmonella Derby positive with six genes, except spvB, whereas Salmonella Albany was positive with only the pagC gene. The comparision of the expression levels of these seven virulent genes and the 16S rRNA control gene showed a significantly difference among Salmonella strains (P<0.05). The result of gene expression of seven virulent genes indicate that Salmonella Hadar has the highest gene expression, followed by Salmonella Enteritidis, Salmonella Derby, Salmonella Typhimurium and finally Salmonella Albany. The results of molecular biology analysis will provide additional data on the expression of virulent genes in Salmonella strains isolated from retail meats in Hanoi.